2013
DOI: 10.1248/bpb.b12-00793
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Absorption and Antibacterial Activities of Lipid Nanocarriers Loaded with Dual Drugs for Acne Treatment

Abstract: The aim of this study was to develop lipid nanocarriers that combine tretinoin and tetracycline for the efficient topical delivery to treat acne vulgaris. Two different nanocarriers, nanoemulsions (NEs) and nanostructured lipid carriers (NLCs), were prepared, and we examined their average size, zeta potential, drug encapsulation percentage, and drug permeation via the skin. The antibacterial activities of the nanosystems against Staphylococcus aureus, Pseudomonas aeruginosa, and Propionibacterium acnes were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…The permeant amount within skin reservoir was extracted by methanol for tretinoin and estradiol or 0.1 N HCl for dextran as described previously (Hsieh et al 2013). The samples of tretinoin and estradiol were analyzed by high performance liquid chromatography (HPLC) (Fang et al 2001;Lin et al 2013). The samples taken from dextran application were quantified by a fluorescence spectrophotometer (F2500, Hitachi, Tokyo, Japan).…”
Section: In Vitro Percutaneous Absorptionmentioning
confidence: 99%
“…The permeant amount within skin reservoir was extracted by methanol for tretinoin and estradiol or 0.1 N HCl for dextran as described previously (Hsieh et al 2013). The samples of tretinoin and estradiol were analyzed by high performance liquid chromatography (HPLC) (Fang et al 2001;Lin et al 2013). The samples taken from dextran application were quantified by a fluorescence spectrophotometer (F2500, Hitachi, Tokyo, Japan).…”
Section: In Vitro Percutaneous Absorptionmentioning
confidence: 99%
“…Since drug molecule basically did not influence the zeta potential (data not shown) and Polysorbate 80 is a non-ionic surfactant, the some ionization and/or hydrolysis of fatty ester groups in Labrafil M1944CS and/or Precirol ATO 5 was possibly responsible for the negative surface charge. 21) According to the literature, when the absolute value of zeta potential for colloidal system is higher than 30 mV, the particles are electrochemically stable under the storage condition because the surface charge prevents aggregation of the particles. 22,23) The NLC aqueous dispersion system showed a high loading efficiency greater than 86%, which indicated that VRC was efficiently incorporated into the lipid particles with their lipophilicity (Log P value of 1.8).…”
Section: Vrc Assay Validationmentioning
confidence: 99%
“…Precirol, composed of fatty esters, possessed amphiphilic properties (20). The surface-active esters could assist in the emulsification process for reducing particle size and creating a rigid interface.…”
Section: Discussionmentioning
confidence: 99%